2013
DOI: 10.5902/217976926638
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de enfrentamento usadas por enfermeiros ao cuidar de pacientes oncológicos

Abstract: RESUMO: Objetivo: conhecer as estratégias que os enfermeiros utilizam para lidar com os abalos psicoemocionais advindos do processo de cuidado de pacientes oncológicos. Método: abordagem qualitativa, descritiva. Realizou-se entrevista aberta, com depoimento de nove enfermeiros, de um hospital oncológico da Zona da Mata Mineira, em Janeiro e Fevereiro de 2012. Da análise compreensiva com aproximação à fenomenologia emergiu que: os enfermeiros se comportam de maneiras distintas frente ao sofrimento e perspectiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
19

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
1
6
0
19
Order By: Relevance
“…4 Reports also revealed that rationalization was seen by nurses as a strategy to deal with routine work in oncology. 13 A similar finding was observed in a study performed with nurses working in pediatric oncology, according to whom the concern about doing "all that can be done" for a patient and their family enabled workers to feel at peace. However, when health care actions were inefficient to alleviate children's pain and suffering, workers experienced feelings of guilt and helplessness.…”
Section: [] I Try To Remind Myself That Everyone Did What They Cousupporting
confidence: 67%
See 1 more Smart Citation
“…4 Reports also revealed that rationalization was seen by nurses as a strategy to deal with routine work in oncology. 13 A similar finding was observed in a study performed with nurses working in pediatric oncology, according to whom the concern about doing "all that can be done" for a patient and their family enabled workers to feel at peace. However, when health care actions were inefficient to alleviate children's pain and suffering, workers experienced feelings of guilt and helplessness.…”
Section: [] I Try To Remind Myself That Everyone Did What They Cousupporting
confidence: 67%
“…In this study, participants reported that separating their professional life from their personal life was necessary, aiming to prevent that patient care influenced their lives out of the oncological hospital unit. 12,13 This shows that the use of such defensive strategy can be common in other contexts.…”
Section: Individual Defensive Strategies Used In the Pediatric Oncolomentioning
confidence: 85%
“…2 Consequently, taking care of the patient implies recognizing his/her condition of weakness and insecurity by using technical and scientific knowledge reflexively, thus providing effective and humanized care. 3 In this perspective, the nurse is oriented to get fully involved with the care, paying attention not only to the psychobiological needs, but also to the psychosociological and psychospiritual needs. Psycholobiological needs refer to oxygenation, hydration, nutrition, elimination, sleep and rest, body care, motility, mobility, physical integrity, cutaneous and mucous integrity, shelter, sexuality, adjustment (thermal, hormonal, neurological, hydro saline, electrolytic, immunological, cell growth, vascular), perception (visual, olfactory, gustatory, auditory, tactile and painful), environment, and therapeutic.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse cenário, os trabalhadores de enfermagem têm um contato com o paciente e seus familiares, lidam com a morte e processo de luto da família e com o sofrimento dos pacientes (3) . O sofrimento desses profissionais diante da dor do outro é tão significativo que, se não forem encontradas formas de enfrentá-lo, o profissional poderá não ser capaz de desenvolver suas atividades rotineiras e pode vir a adoecer (5) . Assim, o profissional não gera uma descompensação psicopatológica (entendida como uma ruptura do equilíbrio psíquico, que se manifesta pela eclosão de uma doença mental), quando o sujeito emprega defesas contra esse sofrimento, que lhe permitem controlá-lo (6) .…”
Section: Introductionunclassified
“…As estratégias de defesa são meios utilizados, pelo trabalhador, para proteger-se do sofrimento; podem surgir frente a situações rotineiras e são vistas como uma maneira de não deixar que a assistência ao indivíduo influencie a vida do profissional fora da unidade hospitalar (5) .…”
Section: Introductionunclassified